The Influence of Corporate Social Responsibility, Good Corporate Governance, and Environmental Performance on Corporate Value (Empirical Study of Manufacturing Companies on the Indonesia Stock Exchange (IDX) Period 2016-2020) - Debby Emira; Ahmad Cik; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This research aims to analyze the impact of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG) featuring an Independent Board of Commissioners, and Environmental Performance on the proper valuation of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The study employs purposive sampling, selecting 16 companies from the population of flat manufacturing companies on the IDX. Secondary data, sourced from annual financial statements on the IDX official website (www.idx.com) for the years 2016-2020, form the basis of the analysis. The findings indicate that: (1) CSR does not significantly affect Company Value, (2) GCG significantly influences Company Value, (3) Environmental Performance significantly impacts Company Value, and (4) collectively, CSR, GCG, and Environmental Performance exhibit a positive and significant influence on Company Value, with a coefficient of determination of 41.1%.